Rheological characterization of powder injection molding compounds - Hausnerová, B. (Polimery, 2021)
This review concerns the rheological research related to compounds obtained using powder injection molding (PIM) technology. PIM is a process for making metallic and ceramic items using forming method for thermoplastics. This technique allows the large-number production of relatively small (corresponding to a weight of around 100 grams) parts of complex shapes with reduced cost comparing to traditional metallurgy and increased efficiency by avoiding the use of extra processes. On the other hand, the number of process variables is very high, and their interactions are only partially understood. The knowledge of the flow properties is the key factor for successful injection molding. Its novelty consists in the polymer physics aspects of the problem, considering the compounds obtained in PIM process as polymer melts highly filled with powder particles.